Interelasi keterampilan bahasa Indonesia lisan dan tulisan bagi tenaga kerja asing di PT. XYZ Purwakarta - Occe Luciana (Peneliti.net, 2022)
Every learning activity certainly requires a test to see how far the participants follow the study. Likewise with the foreign workers at PT. XYZ who took part in Indonesian language learning in each of their offices. They took an Indonesian language proficiency test to test the oral and written Indonesian competence which was held by the author. The test results are related to the length of work of the foreign workers, and after being tested using the Chi-Square Test the conclusion showed p-value = 0.000 <0.05, which means that there is an interrelation between the fluency of the spoken and written of the foreign workers at PT. XYZ. The results of statistical analysis showed the p-value = 0.014 <0.05, meaning that there was a relation between length of work in Indonesia and the oral skills of foreign workers at PT. XYZ. The results of statistical analysis showed that the p-value = 0.112 > 0.05, which means that there is no correlation between the length of work in Indonesia and the written skills of the expatriates at PT. XYZ. The UKBI test for expatriates is recommended to do regularly to control their Indonesian language competence. Keywords: Proficiency test, foreign workers, Bahasa language